FORMULATION OF AN AGE STRUCTURED POPULATION MODEL AND ITS REDUCTION TO A MODEL WITH DELAY - López Cruz, Roxana (2007)
The objective of this paper is to study the reduction of an epidemiological simple SI given originally in partial differential equations into a model in delay differential equations. Originally, the population is divided in juvenile and adult groups. We assume that only the adult population is sexually active and that it is possible that infected adults may produce susceptible newborns and infected newborns. The global stability of the SI model in Delay Equations is studied in López-Cruz [5]